Does the village community have autonomy? between constitutional recognition and international law - Sirajuddin; Al-Fatih, Sholahuddin (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: Although villages existed before the formation of the Unitary State of the Republic of Indonesia, constitutional provisions on village autonomy remain marginal and inconsistent after four amendments to the 1945 Constitution. This undercuts recognition of indigenous communities and meaningful participation, despite converging international doctrines that safeguard collective identity, self-governance, and local decision-making. Purpose/Study Objectives: This study argues that any future constitutional amendment must explicitly recognize and accommodate the autonomy of village communities. It aims to articulate a paradigm of village autonomy embedded in a social-constitution framework that realizes just and equitable prosperity, aligns with international legal standards on indigenous peoples’ rights and participatory governance, and provides clear guidance for normative and operational reform. Design/Methodology/Approach: Using a normative juridical method with descriptive-analytic specification, the research combines statutory and legal-historical approaches with targeted comparative analysis of jurisdictions that constitutionally entrench local or indigenous self-governance. International legal principles are employed as evaluative benchmarks to assess Indonesian constitutional design choices and to distil transferable safeguards (recognition, participation, jurisdiction, and fiscal arrangements). Findings: Future villages should be constitutionally recognized as autonomous and self-sufficient communities that preserve local wisdom, ensure economic stability, and foster locally rooted growth. A reform blueprint emerges: (i) explicit constitutional status for village communities; (ii) delineated competences and guaranteed participation procedures; (iii) stable fiscal architecture; and (iv) safeguards against re-centralization. These elements uphold citizen values and constitutional ethics while harmonizing Indonesian practice with international doctrines on indigenous rights and democratic participation, thus offering actionable pathways for amendment text and implementing legislation. Paper Type: Research Article